Pengembangan Media Pembelajaran Trainer Elektronika Daya di Laboratorium Vokasional Teknik Elektro - Ahmad Denny Listiyawan; Irwanto Irwanto; Mohammad Fatkhurrokhman (Departement of Mathematics Education, 2023)
This study aims to: (1) Know the stages of developing and designing a power electronics trainer. (2) Knowing the feasibility test of a power electronics trainer in terms of media experts and material experts as a tool in power electronics courses. (3) Knowing student responses regarding power electronics trainers as learning media in power electronics courses. This research is a Research and Development (R&D) study with a Four-D model (Define, Design, Development, Dissemination). The subjects of this study were 2 expert lecturers, 2 electronics teachers, 1 electrical technician and electrical engineering vocational education students who had carried out power electronics practices. The research results obtained in the feasibility test in this study obtained a score from media experts, namely 93% with a very feasible category, a score from material experts 97% with a very feasible category, and an assessment from respondents with a score of 87% with a very feasible category.